Pengaruh Kecerdasan Spiritual dan Keharmonisan Keluarga terhadap Kecenderungan Kenakalan Remaja Di MTs Negeri 1 Jombang - Siswati Siswati; Adibah Adibah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to determine the effect of spiritual intelligence and family harmony on the tendency of juvenile delinquency in MTs Negeri 1 Jombang. Sampling using random cluster sampling technique, namely class VIII-B with 32 students. Collecting data using a spiritual scale, harmony scale and juvenile delinquency scale which refers to a Likert scale. The data analysis technique used non-parametric analysis of Spearman's rho level correlation. The results of the influence of the spearman's rho level between spiritual and delinquency were obtained rho = 0.195 and sig 0.285 (P> 0.05), meaning that there was no significant negative relationship between spirituality and delinquency in class VIII-B students of MTs Negeri 1 Jombang. The results of the influence of the spearman's rho level between harmony and delinquency were rho = 0.460 and sig 0.03 (P <0.05), which means that there is a significant positive relationship between harmony and delinquency in class VIII-B students of MTs Negeri 1 Jombang. The higher the krluarga harmony, the lower the juvenile delinquency tendency and conversely the lower the family harmony, the higher the juvenile delinquency tendency.